The Sistem Pakar Deteksi Down Syndrome pada Balita Menggunakan Dempster Shafer dengen Penelusuran Forward Chaining - Rianti Surya Sukatma; Apriade Voutama; Rini Mayasari (Jurnal Ilmiah Wahana Pendidikan, 2022)
Down Syndrome is one of the genetic disorders that begins from the development of the fetus in pregnant women. This is due to the different number of chromosomes 21 than usual. This Down Syndrome results in a delay in the growth and development of the child both psychologically and psychically. The appearance of Down Syndrome is very characteristic of facial figures. However, many parents do not know for sure about this. This expert system of detection of Down Syndrome in toddlers has expert knowledge of pediatric specialists who can help parents to realize if the child has the characteristics of Down Syndrome. The mathematical calculation of the diagnosis of Down Syndrome uses Dempster Shafer which is closely related to uncertainty. This is because for the validation of Down Syndrome, you must do a chromosome test test in the hospital. The Down Syndrome detection expert system is website-based with Forward Chaining tracing. The system will calculate the percentage of diagnoses based on the answers to the symptoms selected by the parents and produce an output in the form of the highest percentage of confidence from the existing calculations.